2006
DOI: 10.2466/pr0.99.1.93-96
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Greek Nursing and Medical Personnel

Abstract: The relatively low number of nurses compared to physicians in Greece and the few available studies on the psychological problems of the health professionals led to comparison of anxiety and depression for 76 Greek nursing personnel (20 men, M age: 32.8 yr., SD: 3.8 yr., and 56 women, M age: 36.6 yr., SD: 7.7 yr.) and 66 doctors (35 men, M age: 35.9 yr., SD: 8.9 yr. and 31 women, M age: 32.7 yr., SD: 8.1 yr.) using validated translations of the Spielberger State-Trait Anxiety Inventory and the Beck Depression I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
(16 reference statements)
0
13
1
Order By: Relevance
“…The prevalence of depression among outpatients with COPD is substantially greater than lifetime rates in the general population (ranging between 10% and 42% in the former, compared to approximately 5% in the latter). Correspondingly, the prevalence of anxiety varies from 10% to 19% [26], a percentage that is higher than the 15% reported in the general population [27,28]. Higher predominance of depression and anxiety was observed in patients with COPD compared to patients that suffered from other chronic respiratory disorders, such as bronchial asthma and tuberculosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of depression among outpatients with COPD is substantially greater than lifetime rates in the general population (ranging between 10% and 42% in the former, compared to approximately 5% in the latter). Correspondingly, the prevalence of anxiety varies from 10% to 19% [26], a percentage that is higher than the 15% reported in the general population [27,28]. Higher predominance of depression and anxiety was observed in patients with COPD compared to patients that suffered from other chronic respiratory disorders, such as bronchial asthma and tuberculosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the positive correlation between anxiety and depression is a common finding in both the general population [5,20] and in patients with COPD [1,6,68]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies in Greece also report high prevalence rates of depression in COPD patients, often above 42% [1]. Moreover, studies indicate rates of anxiety varying from 10% to 19% [3], which is higher than the prevalence rate of 15% mentioned in the general population [5]. Additionally, one out of two patients with COPD disease appears to suffer from general psychopathological symptoms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that while normal levels of stress were present in most physicians, a disproportionate number of emergency physicians reported high levels of stress and depression and thoughts of abandoning their specialty [25]. Likewise, the few studies on the psychological problems of health professionals in Greece revealed high percentages of anxiety and depression in the medical sector [26,27]. …”
Section: Discussionmentioning
confidence: 99%